From Rural to Digital. Insights from Airbnb Gastro-Experiences in Italian Inner Areas - Colangelo, Michaela; Salvatore, Rita (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2024)
The study here presented applies the concepts of countryside capital and nexogenous development to assess the impacts of gastro-tourism offerings through Airbnb’s Experiences platform—an offshoot of the company’s original accommodation model. Experiences are a compilation of activity-based offerings, with the aim of highlighting more ‘authentic’ services to tourists in coherence with local cultural heritage. The research narrows in on one category of these Experiences—food and drink offerings—with the intention of understanding how their proliferation, via this digital platform, has impacted sustainable development across rural and inner communities throughout Italy. Has Airbnb’s new initiative achieved the aim of supporting the enhancement of local heritage in a socially and economically sustainable way? How this proliferation has triggered new forms of rural gastro-tourism, if at all? What role could innovative What role could innovative digital platforms like Airbnb play in driving rural development efforts in terms of nexus? These are the main research questions posed throughout the study. Employing a mixed-methods approach, insights from three different case studies have been drawn. After a detailed desk mapping of all Italian gastronomic Experiences, field work was conducted during the summer of 2022, which entailed in-depth, semi-structured interviews with tourism providers, along with survey responses from rural tourism Experience Hosts. Ultimately, the researchers found that the strategy proposed by Airbnb may one day support a successful, innovative rural development strategy if it can successfully address the threats posed to social, environmental, and economic sustainability, and better incorporate local participation into its business model.